2001
DOI: 10.2134/agronj2001.934936x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Regulator Effects on Spring Cereal Root and Shoot Growth

Abstract: resulting in more efficient water extraction from the deeper soil layers and thereby higher grain yield. How-Plant growth regulators (PGR) shorten the straw of cereals, but ever, Bragg et al. (1984) and Steen and Wü nsche (1990) their effects on other traits of plant stand structure have been inconsistent. To arrive at an assessment of whole-plant response, experiments did not record significant yield increases as a consewere conducted in the greenhouse to study the effect of PGR applica-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(71 citation statements)
references
References 25 publications
7
59
0
5
Order By: Relevance
“…Tiller production increased by TE application; these results are in agreement with the findings of other researchers (Ervin and Koski, 1998;Fagerness et al, 2002;Qian and Engelke, 1999;Rajala and Peltonen-Sainio, 2001) who found that application of TE increased turf density of treated turfgrasses compared with the control. The increase in the number of tillers as a result of using TE may be attributed to the role of these growth regulators in increasing available photoassimilates and cytokinin levels which enhanced cell division involved in the initiation and growth of new tillers from auxiliary meristems, consequently increasing tillering in turfgrasses (Ervin and Zhang, 2007;Pessarakli, 2008;Rajala and Peltonen-Sainio, 2001). Ervin and Koski (1998) reported that tiller production in perennial ryegrass (Lolium perenne L.) treated with TE increased by 67.9% compared with the non-treated control.…”
Section: Tiller Productionsupporting
confidence: 92%
“…Tiller production increased by TE application; these results are in agreement with the findings of other researchers (Ervin and Koski, 1998;Fagerness et al, 2002;Qian and Engelke, 1999;Rajala and Peltonen-Sainio, 2001) who found that application of TE increased turf density of treated turfgrasses compared with the control. The increase in the number of tillers as a result of using TE may be attributed to the role of these growth regulators in increasing available photoassimilates and cytokinin levels which enhanced cell division involved in the initiation and growth of new tillers from auxiliary meristems, consequently increasing tillering in turfgrasses (Ervin and Zhang, 2007;Pessarakli, 2008;Rajala and Peltonen-Sainio, 2001). Ervin and Koski (1998) reported that tiller production in perennial ryegrass (Lolium perenne L.) treated with TE increased by 67.9% compared with the non-treated control.…”
Section: Tiller Productionsupporting
confidence: 92%
“…Em cereais de inverno, o princípio ativo etil-trinexapac vem sendo utilizado em lavouras comerciais no Brasil, e seu uso tem sido indicado para a redução do crescimento das plantas em altura e para o fortalecimento dos entrenós. Embora haja escassez de informações científicas sobre os efeitos do uso de reguladores de crescimento na cultura da aveia-branca, essa prática pode ser uma alternativa para minimizar os efeitos negativos do acamamento de plantas (Rajala & Peltonen-Sainio, 2001;Rajala, 2004;Witkowicz, 2010).…”
Section: Introductionunclassified
“…Such measures can be divided into three main categories: (i) the selection and breeding of genotypes with improved drought tolerance; (ii) an increase in the soil retention capacity and reduction of evaporation from soil surface, and (iii) cultivation measures improving the efficient use of water by plants, which include, for example, the use of growth regulators. In general, the growth regulators can contribute to improving effective use of water in particular by increasing the rooting depth or root water extraction from soil (Marcum and Jiang 1997), increasing the root:shoot ratio (Rajala and Peltonen-Sainio 2001), reducing leaf area (Beasley et al 2007) and accumulation of osmoregulatory substances (Akram et al 2012), increasing the accumulation of antioxidants (Wu and von Tiedemann 2001), supporting stomatal regulation (Bingham and McCabe 2006), reducing rate of leaf senescence (Cromey et al 2004) etc. However, very often contradictory effects of plant regulators on plant physiology and yield formation under water deficit are reported (e.g.…”
mentioning
confidence: 99%